GHIDUL IUBITORILOR DE FOLCLOR (THE GUIDE OF THE FOLKLORE LOVERS), 1/2011, PUBLISHING BY ED. LIDANA, SUCEAVA (ISSN: 2284-5593) - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
In 2011 The Bucovina Cultural Centre – a Centre for Preservation and Promoting of the Traditional Culture launched a new reactivation project of the traditional folkloric creation from Bucovina. This project was initiated by the head of the department - Călin Brăteanu, and the achiever musicologist dr., artistic consultant Constanţa Cristescu. The project of the reactivation of the traditional folkloric creation from Bucovina aimed the following: 1. the contemporary forms of artistic practice, and of scenically reconstitution; 2. the printing of specialized volumes addressed equally to lovers of folklore, as well to the unknowing peoples, to the practitioners, and to the specialists. One of the first results in this respect is the publishing of the magazine Ghidul iubitorilor de folclor (The Guide of the Floklore Lovers), nr. 1/2011.